2002
DOI: 10.1182/blood-2002-02-0445
|View full text |Cite
|
Sign up to set email alerts
|

The role of SAP in murine CD150 (SLAM)-mediated T-cell proliferation and interferon γ production

Abstract: [SLAM]) is the prototypical member of a growing family of glycoprotein receptors on hematopoietic cells, which includes CD229, CD84, CD244, SF2000/Ly108, SF2001, and 19A(CRACC). [1][2][3][4][5][6][7][8] This "SLAM family" is defined by close sequence homology of the receptors that have one or more cytoplasmic tyrosine motifs with the consensus sequence Thr-(Ile/Val)-pTyr-x-x-Val. [9][10][11] The other members of the family, which do not have cytoplasmic tails (CD48, BCM1-like), are likely to act as ligands, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 56 publications
4
65
0
Order By: Relevance
“…Although CD150-induced activation of Akt phosphorylation was observed in T and B lymphocytes 20,22 , UV-inactivated vaccine strain of MV was shown to inhibit IL-2 dependent activation of Akt pathway in T cells 33 . These disparities may be linked to differences in the cell types and viral strains, distinct mode of cell activation and finally surface interaction of lymphocytes with the MV glycoprotein complex independently of CD150.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although CD150-induced activation of Akt phosphorylation was observed in T and B lymphocytes 20,22 , UV-inactivated vaccine strain of MV was shown to inhibit IL-2 dependent activation of Akt pathway in T cells 33 . These disparities may be linked to differences in the cell types and viral strains, distinct mode of cell activation and finally surface interaction of lymphocytes with the MV glycoprotein complex independently of CD150.…”
Section: Discussionmentioning
confidence: 99%
“…As PI3K/ Akt pathway is one of the signaling pathways linked to CD150 engagement in lymphocytes 20,22 , we have assumed that MV may also trigger Akt in monocyte-derived human DCs. Our previous studies demonstrated that both infectious and UV-inactivated MV particles, in addition to the presence of viral envelope glycoproteins, contain an important quantity of free MV nucleoprotein, which can stimulate Fc receptor expressed on numerous cells, including DCs 34,35 .…”
Section: Mv-h Interaction With Cd150 Increases Akt Phosphorylation Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that macrophage functions in SLAM-deficient mice have previously been shown to be impaired (7), we cannot exclude the possibility that this cell type may contribute to the failure of SLAM-deficient mice to develop allergic responses. A recently described receptor for SLAM, termed SLAM-associated protein, has been identified (27). Whether SLAM-mediated effects in allergic asthma predominate by lymphocyte, macrophage, or SLAM-associated protein signaling-mediated mechanisms warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Because engagement of CD150 or CS1 was shown to trigger PI3K activation (17,(33)(34)(35), and this activation is mediated by EAT-2 in NK cells (17), we hypothesized that EAT-2 acts downstream of SLAM engagement to decrease IL-12 production in BMDC by blocking activation of the p38 MAPK and JNK pathways, through activation of the PI3K pathway. Consistent with this possibility, engagement of CD150 or CD84 led to significantly reduced levels of p38 MAPK and JNK, as well as increased levels of AKT phosphorylation following CD40 stimulation of BMDC, which was not seen for c1 congenic mouse strains with the NZB EAT-2 polymorphism.…”
Section: Discussionmentioning
confidence: 99%